PAPAN PARTIKEL DARI LIMBAH SERUTAN ROTAN DAN CANGKANG SAWIT - Budi Tri Cahyana (Jurnal Riset Industri Hasil Hutan, 2013)
The research of particle board for interior purpose with the mixed composition of rattan shavings (as core) and oil palm shell (the outer layer) had been done. Those composition consisted of a1= 30%: 40%: 30%, a2= 25%:50%:25%, a3= 20%, 60%, 20%, a4= 15%:70%:15%, a5= 10%:80%,10%,  a6= 5%:90%:5%. The concentration of Urea Formaldehida (UF) adhesive were b1=3%, b2= 6%, b3=9%. The physical and mechanical properties of particles board showed that water content 11,12% - 11,71%, the development of thickness 5,56% - 7,15%, water absorption 18,04% - 23,46%, density 0,52 g/cm3 – 0,71 g/cm3, Modulus of Elasticity (MOE) 128 kg/cm2 – 697 kg/cm2, Module of Rufture (MOR) 52 kg/cm2 – 106  kg/cm2. The higher the concentration of raw materials of rattan shavings nor UF adhesive, the better quality of partcle board, included in the criteria for medium density of flat particle board. The resulted particle boards meet requirements of Indonesian National Standard for flat particle board SNI 03-2105-2006.Keywords:  particle board, rattan shaving, oil palm shell